A concrete graphene surface treatment agent and its application

By developing a graphene surfactant, the graphene powder is dispersed with surfactant, epoxy resin and organic solvent, and mixed with stone powder and silicon powder, the problem of high graphene consumption and high cost in the prior art is solved, significantly improving the wear resistance of concrete and reducing cracking.

CN119752280APending Publication Date: 2025-04-04CHONGQING GRAPHENE RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954198.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

When the prior art mixes graphene with concrete to improve performance, there are problems such as large amount of graphene and high overall cost, which makes it difficult to effectively improve the wear resistance of concrete and reduce cracking.

Method used

A graphene surfactant was developed to disperse the graphene powder by selecting suitable surfactants, epoxy resins and organic solvents and mix them with stone powder and silicon powder to prepare a treatment agent for spraying on the concrete surface.

Benefits of technology

The wear resistance of concrete is significantly improved. According to the test results, the wear amount of 28 days is reduced by about 40% compared with the untreated concrete, and the cracking of concrete is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215501810000051
    Figure BDA0005215501810000051
  • Figure BDA0005215501810000061
    Figure BDA0005215501810000061
Patent Text Reader

Abstract

The present invention belongs to the technical field of concrete surface treatment, and specifically relates to a concrete graphene surface treatment agent and its application. The surface treatment agent includes a graphene dispersion and an auxiliary agent, wherein the graphene dispersion includes an epoxy resin, a graphene powder, a surfactant and an organic solvent, wherein the surfactant selects hexadecylpyridinium chloride and / or sodium dodecylbenzenesulfonate; the auxiliary agent includes stone powder and silicon powder. After treating the concrete surface with the concrete graphene surface treatment agent provided by the present invention, the wear resistance can be significantly improved. According to the test of JTG 3420-2020 "Test Procedure for Cement and Cement Concrete in Highway Engineering", it can be learned that the 28d wear amount is reduced by about 40% compared with untreated concrete, and the concrete will not produce obvious cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete surface treatment, and specifically relates to a concrete graphene surface treatment agent and application thereof. Background Art

[0002] As a widely used building material, the optimization of concrete's performance has always been the focus of attention in the construction field. With the advancement of science and technology, more and more new materials are being used to improve the performance of concrete. As one of the new materials, graphene has received extensive attention in the field of building materials in recent years due to its high electrical conductivity, high thermal conductivity, high mechanical strength and high specific surface area. Among them, especially the high mechanical strength of graphene, it can significantly improve the wear resistance, one of the important indicators of concrete.

[0003] Currently, graphene is used in concrete to improve its performance by placing graphene and concrete raw materials into a mixer and dispersing the graphene evenly in cement concrete through mechanical mixing; however, this method has the problem of large amount of graphene used and high overall cost.

[0004] Therefore, it is necessary to develop a graphene surface treatment agent that can be directly used on the concrete surface. Summary of the invention

[0005] The present invention develops a graphene surface treatment agent for concrete surface treatment. In fact, the graphene powder is dispersed by selecting a suitable surfactant in combination with an epoxy resin and an organic solvent, and then mixed with stone powder and silicon powder. The prepared surface treatment agent can significantly improve the wear resistance of concrete and reduce cracking by treating the concrete surface.

[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:

[0007] On one hand, the present invention provides a concrete graphene surface treatment agent, which comprises a graphene dispersion and an additive. The graphene dispersion comprises an epoxy resin, graphene powder, a surfactant and an organic solvent, wherein the surfactant is selected from hexadecylpyridinium chloride and / or sodium dodecylbenzene sulfonate; and the additive comprises stone powder and silicon powder.

[0008] Preferably, the organic solvent is selected from one or more combinations of N,N-dimethylformamide, dibutyl phthalate, toluene, xylene or ethyl acetate; and / or the particle size of the stone powder is ≤0.075mm; and / or the particle size of the silicon powder is ≤800nm.

[0009] Preferably, in the above graphene dispersion, the mass proportion of epoxy resin is 20%-30%, the mass proportion of graphene powder is 5%-10%, the mass proportion of surfactant is 0.7%-5%, and the balance is organic solvent.

[0010] More preferably, in the above graphene dispersion, the mass proportion of epoxy resin is 25%, the mass proportion of graphene powder is 7%, the mass proportion of surfactant is 2%, and the balance is organic solvent.

[0011] Preferably, the mass of the stone powder is 15%-25% of the mass of the graphene dispersion; and / or the mass of the silicon powder is 5%-20% of the mass of the graphene dispersion.

[0012] More preferably, the mass of the stone powder is 20% of the mass of the graphene dispersion; and / or the mass of the silicon powder is 15% of the mass of the graphene dispersion.

[0013] Another aspect of the present invention provides an application of the concrete graphene surface treatment agent of the present invention in a concrete surface.

[0014] Preferably, in the above application, the concrete comprises, by weight, 290-330 parts of cement, 590-700 parts of machine-made sand, 1290-1340 parts of crushed stone, 120-143 parts of water and 1-3 parts of water reducing agent.

[0015] Preferably, the above application method is to spray the concrete graphene surface treatment agent after vibrating the concrete and before kneading the concrete.

[0016] More preferably, the spraying amount of the above concrete graphene surface treatment agent is 1g / m 2 -20g / m 2 .

[0017] The beneficial effects of the present invention include:

[0018] (1) The concrete graphene surface treatment agent provided by the present invention can be directly sprayed on the concrete surface after the concrete is vibrated and before the concrete is kneaded, which is different from the prior art in which the concrete is mixed with the concrete to improve the performance of the concrete.

[0019] (2) After treating the concrete surface with the concrete graphene surface treatment agent provided by the present invention, the wear resistance can be significantly improved. According to the test of JTG 3420-2020 "Test Procedure for Cement and Cement Concrete for Highway Engineering", it can be found that the 28d wear amount is reduced by about 40% compared with the untreated concrete, and the concrete will not produce obvious cracks. DETAILED DESCRIPTION

[0020] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.

[0021] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.

[0022] The embodiment of the present invention provides a concrete graphene surface treatment agent, which includes a graphene dispersion and an additive. The graphene dispersion includes an epoxy resin, graphene powder, a surfactant and an organic solvent, wherein the surfactant is selected from hexadecylpyridinium chloride and / or sodium dodecylbenzene sulfonate; the additive includes stone powder and silicon powder.

[0023] It should be noted that the present invention found that dispersing graphene in a surfactant, a surfactant and an organic solvent, and then mixing it with stone powder and silicon powder can enhance the wear resistance of concrete; and it was found that the selection of surfactant has a great influence on the improvement of performance. The present invention selected surfactants cetylpyridinium chloride or sodium dodecylbenzene sulfonate, which have a great improvement on the concrete surface, especially the surfactant cetylpyridinium chloride; while some surfactants do not have the effect of improving performance, such as polyethylene glycol octylphenyl ether and tetradecyl dimethyl betaine. It may be that these two surfactants cannot make the graphene powder evenly dispersed in the system, resulting in the inability to improve performance.

[0024] In some specific examples, the organic solvent is selected from one or more combinations of N,N-dimethylformamide, dibutyl phthalate, toluene, xylene or ethyl acetate; and / or the particle size of the stone powder is ≤0.075mm; and / or the particle size of the silicon powder is ≤800nm.

[0025] It should be noted that the stone powder in the present invention can enhance the water retention and cohesion of concrete to a certain extent, thereby improving the wear resistance and crack resistance of concrete; and the silica powder can directly participate in the volcanic ash reaction of cement, improve the degree of hydration, and fill the pores of the hydration product for the nano-silicon powder that does not participate in the reaction or the excess, so that the structure of the cement stone is more compact, thereby enhancing the wear resistance and crack resistance of concrete; in addition, the particle size of the stone powder in the present invention is ≤0.075mm, such as ≤0.07mm, ≤0.06mm or ≤0.05mm, etc.; the particle size of the silica powder is ≤800nm, such as ≤700nm, ≤600nm or ≤500nm, etc.

[0026] In some specific examples, in the above graphene dispersion, the mass proportion of epoxy resin is 20%-30%, the mass proportion of graphene powder is 5%-10%, the mass proportion of surfactant is 0.7%-5%, and the balance is organic solvent.

[0027] In some specific examples, in the above-mentioned graphene dispersion, the mass proportion of epoxy resin is 27%, the mass proportion of graphene powder is 5%, the mass proportion of surfactant is 1.5%, and the balance is organic solvent; or the mass proportion of epoxy resin is 24%, the mass proportion of graphene powder is 6%, the mass proportion of surfactant is 2%, and the balance is organic solvent; or the mass proportion of epoxy resin is 29%, the mass proportion of graphene powder is 3%, the mass proportion of surfactant is 3%, and the balance is organic solvent.

[0028] It should be noted that the amount of epoxy resin, graphene powder and surfactant will affect the treatment effect of the surface treatment agent, among which, the preferred mass proportion of epoxy resin is 25%, the mass proportion of graphene powder is 7%, the mass proportion of surfactant is 2%, and the balance is organic solvent; the concrete treated with the surface treatment agent prepared under this ratio has less wear and less cracking.

[0029] In some specific examples, the mass of the above-mentioned stone powder is 15%-25% of the mass of the graphene dispersion, such as 17%, 19%, 21% or 23%, etc.; and / or the mass of the above-mentioned silicon powder is 5%-20% of the mass of the graphene dispersion, such as 7%, 11%, 13%, 15%, 17% or 19%, etc.

[0030] It should be noted that the amount of stone powder and silicon powder used also has a significant effect on the treatment performance of the surface treatment agent. Too little or too much will significantly affect the treatment effect. In the present invention, it is preferred that the mass of stone powder is 20% of the mass of the graphene dispersion liquid and the mass of silicon powder is 15% of the mass of the graphene dispersion liquid. The concrete treated with the surface treatment agent prepared under this ratio has less wear and less cracking.

[0031] An embodiment of the present invention also provides an application of the concrete graphene surface treatment agent of the present invention in a concrete surface.

[0032] It should be noted that using the concrete graphene surface treatment agent of the present invention on the concrete surface can significantly improve the wear resistance and cracking degree of the concrete.

[0033] In some specific examples, in the above application, the concrete includes, by weight, 290-330 parts of cement, 590-700 parts of machine-made sand, 1290-1340 parts of crushed stone, 120-143 parts of water, and 1-3 parts of water reducing agent.

[0034] It should be noted that the concrete graphene surface treatment agent of the present invention is suitable for all concretes with insufficient wear resistance and severe cracking, such as the concrete prepared with the above formula.

[0035] In some specific examples, the above application method is to spray the concrete graphene surface treatment agent after vibrating the concrete and before kneading the concrete.

[0036] In some specific examples, the spraying amount of the above concrete graphene surface treatment agent is 1g / m 2 -20g / m 2 , such as 3g / m 2 -15g / m 2 , 7g / m 2 -12g / m 2 , or 8g / m 2 -11g / m 2 wait.

[0037] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.

[0038] In the following examples, the stone powder is purchased from Chaoyang Jianyuan New Materials Technology Co., Ltd. and is a fabric stone powder; the silicon powder is nano silicon powder purchased from Beijing Dekedaojin Technology Co., Ltd., model DK-Si-001; the epoxy resin is purchased from Shandong Pinshang New Materials Co., Ltd. Fengguang brand E-44 (6101).

[0039] 1. Preparation of concrete surface treatment agent

[0040] Example 1

[0041] (1) Preparation of graphene dispersion

[0042] Epoxy resin is dissolved in N,N-dimethylformamide, and after mixing evenly, graphene powder and hexadecylpyridinium chloride are added and stirred to mix evenly to obtain a graphene dispersion.

[0043] The addition amounts of epoxy resin, N,N-dimethylformamide, graphene powder and hexadecylpyridinium chloride are shown in Table 1 below.

[0044] Table 1 Example 1 Graphene dispersion raw material ratio

[0045] Components Weight(g) Epoxy resin 100 Graphene powder 25 Hexadecylpyridinium chloride 3.5 N,N-Dimethylformamide Add to 500g

[0046] (2) Preparation of concrete surface treatment agent

[0047] Take 200 g of the graphene dispersion prepared above, add 40 g of stone powder and 30 g of silicon powder, mix and stir to prepare a concrete surface treatment agent.

[0048] Example 2

[0049] The difference between Example 3 and Example 1 is that the raw material ratio of the graphene dispersion liquid in Example 2 is different from that in Example 1, and the rest is the same as Example 1; the raw material ratio of Example 2 is shown in Table 2 below.

[0050] Table 2 Example 2 Graphene dispersion raw material ratio

[0051] Components Weight(g) Epoxy resin 125 Graphene powder 35 Hexadecylpyridinium chloride (2%) 10 N,N-Dimethylformamide Add to 500g

[0052] Example 3

[0053] The difference between Example 3 and Example 1 is that the raw material ratio of the graphene dispersion liquid in Example 3 is different from that in Example 1, and the rest is the same as Example 1; the raw material ratio of Example 3 is shown in Table 3 below.

[0054] Table 3 Example 3 Graphene dispersion raw material ratio

[0055] Components Weight(g) Epoxy resin 150 Graphene powder 50 Hexadecylpyridinium chloride 25 N,N-Dimethylformamide Add to 500g

[0056] Example 4

[0057] The difference between Example 4 and Example 2 is that the surfactant in Example 4 is different from that in Example 2, and the rest is the same as Example 2; the raw material ratio of Example 4 is shown in Table 4 below.

[0058] Table 4 Example 4 Graphene dispersion raw material ratio

[0059]

[0060]

[0061] Example 5

[0062] The difference between Example 5 and Example 2 is that the added amounts of stone powder and silicon powder are different. The other aspects are the same as Example 2. In Example 5, the added amount of stone powder is 30 g, and the added amount of silicon powder is 10 g.

[0063] Example 6

[0064] The difference between Example 6 and Example 2 is that the added amounts of stone powder and silicon powder are different. The other aspects are the same as Example 2. In Example 5, the added amount of stone powder is 50 g, and the added amount of silicon powder is 40 g.

[0065] Comparative Example 1

[0066] The difference between Comparative Example 1 and Example 2 is that the surfactant in Comparative Example 1 is different from that in Example 2, and the rest is the same as Example 2; the raw material ratio of Comparative Example 1 is shown in Table 5 below.

[0067] Table 5 Comparative Example 1 Graphene dispersion raw material ratio

[0068] Components Weight(g) Epoxy resin 125 Graphene powder 35 Polyethylene glycol octylphenyl ether (2%) 10 N,N-Dimethylformamide Add to 500g

[0069] Comparative Example 2

[0070] The difference between Comparative Example 2 and Example 2 is that the surfactant in Comparative Example 2 is different from that in Example 2, and the rest is the same as Example 2; the raw material ratio of Comparative Example 2 is shown in Table 6 below.

[0071] Table 6 Comparative Example 2 Graphene dispersion raw material ratio

[0072] Components Weight(g) Epoxy resin 125 Graphene powder 35 Tetradecyl dimethyl betaine (2%) 10 N,N-Dimethylformamide Add to 500g

[0073] 2. Performance test of concrete

[0074] In the following tests, the preparation of concrete includes: 300 parts of cement, 650 parts of machine-made sand, 1300 parts of crushed stone, 135 parts of water and 3 parts of a water reducer (naphthalene-based water reducer FDN-C purchased from Jining Fangyu Chemical Co., Ltd.) are mixed and stirred to prepare concrete.

[0075] The prepared concrete was poured into a prepared mold (150 mm × 150 mm × 150 mm), the concrete was compacted using a vibrating table, and then the surface of the test block was smoothed using a spatula to prepare a concrete blank specimen; in addition, the surface treatment agent prepared in Examples 1 to 6 and Comparative Examples 1 and 2 was used at a concentration of 20 g / m 2 The dosage was evenly sprayed on the concrete, and then the surface of the test block was smoothed with a trowel to prepare different concrete specimens.

[0076] (I) Wear resistance test

[0077] The above-mentioned concrete blank specimens and different concrete specimens were molded and cured according to JTG 3420-2020 "Test Code for Cement and Cement Concrete for Highway Engineering" T 0567 and subjected to wear resistance tests; the test results are shown in Table 7 below.

[0078] Table 7 Wear resistance test results of different concrete specimens

[0079] Grouping <![CDATA[28d wear amount (kg / m 2 )]]> Concrete blank specimen 5.76 Concrete specimens prepared in Example 1 4.34 Concrete specimens prepared in Example 2 3.46 Concrete specimens prepared in Example 3 4.27 Concrete specimens prepared in Example 4 3.73 Concrete specimens prepared in Example 5 4.98 Concrete specimens prepared in Example 6 5.03 Concrete specimens prepared in Comparative Example 1 5.81 Concrete specimens prepared in Comparative Example 2 5.73

[0080] It can be seen from Table 7 that the wear amount of the concrete specimens prepared in Examples 1 to 6 is much smaller than that of the concrete blank specimens and the concrete specimens prepared in the comparative example. Among them, the wear amount of the concrete specimens prepared in Examples 2 and 4 is lower than that of the other examples. Example 2 is the best, and the wear amount is reduced by about 40% compared with the concrete blank specimen. In addition, the wear amount of the concrete specimen prepared in Comparative Example 2 is equivalent to that of the concrete blank specimen; the wear amount of the concrete specimen prepared in Comparative Example 1 is slightly larger than that of the concrete blank specimen.

[0081] (II) Crack resistance test

[0082] The above-mentioned concrete blank specimens and different concrete specimens were formed and cured in accordance with JTG 3420-2020 "Test Procedures for Cement and Cement Concrete for Highway Engineering" T0573 and subjected to crack resistance tests (the crack resistance test was performed by curing the specimens in a standard curing room at 20±2°C and a relative humidity greater than 95% for 3 days after molding, and the cracking conditions on the specimen surface were counted after 3 days); the test results are shown in Table 8 below.

[0083] Table 8 Test results of crack resistance of different concrete specimens

[0084] Grouping Number of cracks The longest crack length (mm) Concrete blank specimen 5 14 Concrete specimens prepared in Example 1 3 7 Concrete specimens prepared in Example 2 0 0 Concrete specimens prepared in Example 3 2 5 Concrete specimens prepared in Example 4 1 4 Concrete specimens prepared in Example 5 4 8 Concrete specimens prepared in Example 6 3 6 Concrete specimens prepared in Comparative Example 1 6 12 Concrete specimens prepared in Comparative Example 2 5 17

[0085] It can be seen from Table 8 that the number of cracks and the length of cracks in the concrete specimens prepared in Examples 1 to 6 are lower than those in the concrete blank specimens and the concrete specimens prepared in the comparative example; among them, Example 2 did not produce any cracks, and Example 4 only produced 1 crack, and the length of the crack was smaller than that of the other concrete specimens; the degree of cracking of the concrete specimens of Comparative Examples 1 and 2 was not much different from that of the concrete blank specimen.

[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.

Claims

1. A concrete graphene surface treatment agent, characterized in that, The invention comprises a graphene dispersion and an auxiliary agent. The graphene dispersion comprises epoxy resin, graphene powder, a surfactant and an organic solvent, wherein the surfactant is selected from hexadecylpyridinium chloride and / or sodium dodecylbenzene sulfonate; and the auxiliary agent comprises stone powder and silicon powder.

2. The concrete graphene surface treatment agent according to claim 1, characterized in that: The organic solvent is selected from one or more combinations of N,N-dimethylformamide, dibutyl phthalate, toluene, xylene or ethyl acetate; and / or the particle size of the stone powder is ≤0.075mm; and / or the particle size of the silicon powder is ≤800nm.

3. The concrete graphene surface treatment agent according to claim 1 or 2, characterized in that: In the graphene dispersion, the mass proportion of epoxy resin is 20%-30%, the mass proportion of graphene powder is 5%-10%, the mass proportion of surfactant is 0.7%-5%, and the balance is organic solvent.

4. The concrete graphene surface treatment agent according to claim 3, characterized in that: In the graphene dispersion, the mass proportion of epoxy resin is 25%, the mass proportion of graphene powder is 7%, the mass proportion of surfactant is 2%, and the balance is organic solvent.

5. The concrete graphene surface treatment agent according to claim 1, 2 or 4, characterized in that: The mass of the stone powder is 15%-25% of the mass of the graphene dispersion; and / or the mass of the silicon powder is 5%-20% of the mass of the graphene dispersion.

6. The concrete graphene surface treatment agent according to claim 5, characterized in that: The mass of the stone powder is 20% of the mass of the graphene dispersion; and / or the mass of the silicon powder is 15% of the mass of the graphene dispersion.

7. Use of the concrete graphene surface treatment agent according to any one of claims 1 to 6 in a concrete surface.

8. The use according to claim 7, characterized in that: Concrete includes, by weight, 290-330 parts of cement, 590-700 parts of machine-made sand, 1290-1340 parts of crushed stone, 120-143 parts of water and 1-3 parts of water reducing agent.

9. The use according to claim 7 or 8, characterized in that: The application method is to spray the concrete graphene surface treatment agent after vibrating the concrete and before kneading the slurry.

10. The use according to claim 9, characterized in that: The spraying amount of concrete graphene surface treatment agent is 1g / m 2 -20g / m 2 .